Photobiomodulation, Depression, Anxiety, and Cognition - Marks, Ray (Journal of Aging Research And Healthcare, 2021)
Background Anxiety and depression are key barriers to healthy aging and greatly heighten the risk for many negative health issues that seriously impact life quality. Aim This mini review examines the potential of low level laser treatments or photobiomodulation therapy for ameliorating severe anxiety and depression in older adults. Methods and Procedures Articles that adressed the current topic of interest extracted from PUBMED and Google Scholar were carefully and presented in narrative form. Results Photobiomodulation therapy appears to be a safe efficacious modality for ameliorating various degrees of anxiety and depression and for improving cognition, and is supported by several well established mechanisms of action at the molecular, cellular, and tissue levels. Conclusion More research to examine who might benefit most from this form of therapy, and in what respect in this area of growing global concern and few intervention options is strongly warranted.
Keywords: Photobiomodulation Therapy; Depression; Anxiety; Cognition; Aging; Low-Level Laser Therapy; Near-Infrared Radiation